Autogenous crisis as a conceptual model of system changes - O. V. Deviatkin (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article introduces a conceptually new line in ensuring the long-time sustainable development of the organization, i.e. autogenous crisis. The notion of ‘crisis’ is analyzed and its forms in different socio-cultural systems are described. Crisis is a concentrated in time and at a certain place crucial, drastic for the system moment of truth, a point of bifurcation – a critical condition of the system, when it becomes unstable. Examples of crises in different social systems show that crisis is an inevitable stage in the life cycle of any living system. During its evolution any living system repeatedly passes a dynamic cycle ‘stability – crisis – new stability’. The author puts forward the thesis that crisis demonstrates the 3-rd law of Hegel dialectics - negation of negation. A conclusion was drawn that crisis breaks a former balance (stability) and at the same time provides an opportunity (potential) of passing-over to a new balance (new stability), i.e. crisis acts as a method of object movement from the former disintegration and conflict to a new condition. Speaking about a practical application of the phenomenon of crisis the author proposes to initiate by top executives of the organization a controlled (autogenous) crisis in order to eliminate contradictions, disproportions and misbalance arising in any living system during its life cycle. The autogenous crisis gives an opportunity to re-load the system and to move to a new level of stability. The conceptual apparatus was developed to resolve the task and goals, object, subject, key principles and components of the notion ‘autogenous crisis’ were defined.